2004
DOI: 10.1111/j.0022-2720.2004.01377.x
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing photobleaching during confocal microscopy of fluorescent probes bound to chromatin: role of anoxia and photon flux

Abstract: SummaryExposure to light can destroy the ability of a molecule to fluoresce. Such photobleaching limits the use of fluorescence and confocal microscopy in biological studies. Loss of fluorescence decreases the signal-to-noise ratio and so image resolution; it also prevents the acquisition of meaningful data late during repeated scanning (e.g. when collecting three-dimensional images). The aim of this work was to investigate the role of oxygen in the photobleaching of fluorophores bound to DNA in fixed cells, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
94
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 64 publications
3
94
0
1
Order By: Relevance
“…1; Tyerman et al 2004). Bondada et al (2005) qualitatively confirmed that xylem hydraulic conductance continued in post veraison berries by demonstrating that dye uptake could still occur provided the appropriate driving force on water flow to the berry could be sustained. Tyerman et al (2004) also showed that the xylem pressure changed from being negative to slightly positive during veraison, supporting the view that the nature of the driving force for water movement to the berry in the xylem changes during phase 2 (Fig.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…1; Tyerman et al 2004). Bondada et al (2005) qualitatively confirmed that xylem hydraulic conductance continued in post veraison berries by demonstrating that dye uptake could still occur provided the appropriate driving force on water flow to the berry could be sustained. Tyerman et al (2004) also showed that the xylem pressure changed from being negative to slightly positive during veraison, supporting the view that the nature of the driving force for water movement to the berry in the xylem changes during phase 2 (Fig.…”
Section: Introductionmentioning
confidence: 63%
“…There has been much interest recently in the water budget of the developing grape berry (Bondada et al 2005;Keller et al 2006;Rogiers et al 2006; Thomas et al 2006;Tilbrook and Tyerman 2006;Zhang et al 2006b). This is for two reasons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the relatively high irradiances that can be used in FCS experiments, effects of excitation to higher singlet and triplet states (S n and T n states) can sometimes be noticed. In particular, from these states, photooxidation and photo-bleaching is typically strongly enhanced 7,[11][12][13] . To describe the generation of photo-oxidized states in the FCS experiments it is therefore motivated to include higher excited states (S n and T n ) into the electronic state model, as outlined in Figure …”
Section: Theorymentioning
confidence: 99%
“…It has been shown that excited fluorophores interact with dissolved oxygen producing reactive oxygen species, such as super oxide radicals (Wright et al, 2002). These can oxidize and destroy a variety of components, such as proteins and their associated fluorophores, leading to a loss of fluorescence signal (Greenbaum et al, 2000;Bernas et al, 2004). For this to happen, oxygen must collide with the excited dye.…”
Section: Applications For Low-temperature Gfp Imaging With Reduced Phmentioning
confidence: 99%